Mechanism of retinoic acid-induced transcription: histone code, DNA oxidation and formation of chromatin loops. Issue 17 (12th September 2014) - Zuchegna, Candida; Aceto, Fabiana; Bertoni, Alessandra; Romano, Antonella; Perillo, Bruno; Laccetti, Paolo; Gottesman, Max E.; Avvedimento, Enrico V.; Porcellini, Antonio
Abstract: Histone methylation changes and formation of chromatin loops involving enhancers, promoters and 3′ end regions of genes have been variously associated with active transcription in eukaryotes. We have studied the effect of activation of the retinoic A receptor, at the RARE–promoter chromatin of CASP9 and CYP26A1 genes, 15 and 45 min following RA exposure, and we found that histone H3 lysines 4 and 9 are demethylated by the lysine-specific demethylase, LSD1 and by the JMJ-domain containing demethylase, D2A. The action of the oxidase (LSD1) and a dioxygenase (JMJD2A) in the presence of Fe++ elicits an oxidation wave that locally modifies the DNA and recruits the enzymes involved in base and nucleotide excision repair (BER and NER). These events are essential for the formation of chromatin loop(s) that juxtapose the RARE element with the 5′ transcription start site and the 3′ end of the genes. The RARE bound-receptor governs the 5′ and 3′ end selection and directs the productive transcription cycle of RNA polymerase. These data mechanistically link chromatin loops, histone methylation changes and localized DNA repair with transcription.